2011
DOI: 10.25011/cim.v34i4.15364
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness and paraoxonase activity in patients with ankylosing spondylitis

Abstract: Purpose: e risk of atherosclerosis is increased in several rheumatological disorders, but any such risk remains unproven for ankylosing spondylitis. Since carotid intima-media thickness is an indicator of early atherosclerosis, and the paraoxonase (PON1) enzyme has antioxidant activity to prevent LDL oxidation, we aimed to identify: 1) the relationship between carotid intima-media thickness (CIMT) and serum paraoxonase (PON1) activity in ankylosing spondylitis (AS) patients; and 2) the possible di erences in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
30
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
8
30
2
Order By: Relevance
“…35 Nakanishi et al 36 used computed tomography to measure EFT levels and reported that patients with high levels had more coronary artery calcification. In studies by Cece et al 12 and Resorlu et al, 37 CIMT values in AS patients were found to be higher than those of the control group. In our study, AS patients had increased EFT thickness with high CIMT values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…35 Nakanishi et al 36 used computed tomography to measure EFT levels and reported that patients with high levels had more coronary artery calcification. In studies by Cece et al 12 and Resorlu et al, 37 CIMT values in AS patients were found to be higher than those of the control group. In our study, AS patients had increased EFT thickness with high CIMT values.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were selected from the Departments of Physical Medicine and Rehabilitation and Cardiology of Abant Izzet Baysal University. They were diagnosed as AS on the basis of Assessment of SpondyloArthritis International Society criteria 5,12 between December 2014 and April 2015. This study was approved by our Institutional Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lange U et al had found that, AS patients' blood inflammatory markers were much higher compared with patients without AS, such as interleukin 6, tumor necrosis factor alpha, and Creactive protein [9]. In addition, in other literatures, AS patients were more likely to associated with early features of atherosclerosis, such as the thickness of intima media of the carotid arteries increased and flow-mediated dilatation of the brachial arteries impaired [10,11]. Therefore, the atherogenesis and plaque formation caused by systemic inflammation may be the reason for higher risk of ischemic stroke in the AS patients.…”
Section: Discussionmentioning
confidence: 99%